Comparison of two multiple plankton samplers: MOCNESS and Multinet Mammoth. (30th August 2022) - Strand, Espen; Broms, Cecilie; Bagøien, Espen; Knutsen, Tor; Arnesen, Hilde; Mozfar, Bahar
Abstract: To ensure an optimal continuation of a long time series of zooplankton monitoring surveys, two types of equipment for depth‐stratified mesozooplankton sampling were compared. The Institute of Marine Research (Norway) has applied the MOCNESS with good results since 1985, but recent events have made it necessary to change to the Multinet Mammoth. During a cruise in March 2019, both sampling devices were calibrated before 17 paired deployments of the 2 gears were undertaken. During each deployment, three nets and depth‐strata covering ~ 425–200, 200–100, and 100–0 m were sampled. All samples were size‐fractionated or taxonomically fractionated into 10 different biomass categories. The results revealed no significant differences between the two gears when comparing total depth‐integrated biomass (2.46 ± 0.36 vs. 2.61 ± 0.59 gDW m −2 ) or depth‐integrated biomass of any specific biomass category. Running paired t ‐tests separately for all combinations of biomass categories and nets, the differences were only significant for zooplankton biomasses in the 180–1000  μ m size fraction and only for Net 2. Possible reasons for this result are discussed in the paper. Gears produced similar catches whether sampling during day or night. We conclude that the MOCNESS and Multinet Mammoth in this study provided comparable results regarding abundances of various zooplankton categories.